Hemoconcentration is associated with early faster fluid rate and increased risk of persistent organ failure in acute pancreatitis patients. Issue 4 (13th March 2020) - Jin, Tao; Li, Lan; Deng, Lihui; Wen, Si; Zhang, Ruwen; Shi, Na; Zhu, Ping; Lan, Lan; Lin, Ziqi; Jiang, Kun; Guo, Jia; Liu, Tingting; et al.
Abstract: Background: Controversies existed surrounding the use of hematocrit to guide early fluid therapy in acute pancreatitis (AP). The association between hematocrit, early fluid therapy, and clinical outcomes in ward AP patients needs to be investigated. Methods: Data from prospectively maintained AP database and retrospectively collected details of fluid therapy were analyzed. Patients were stratified into three groups: Group 1, hematocrit < 44% both at admission and at 24 h thereafter; Group 2: regardless of admission level, hematocrit increased and >44% at 24 h; Group 3: hematocrit >44% on admission and decreased thereafter during first 24 h. "Early" means first 24 h after admission. Baseline characteristics, early fluid rates, and clinical outcomes of the three groups were compared. Results: Among the 628 patients, Group 3 had a higher hematocrit level, greater baseline predicted severity, faster fluid rate, and more fluid volume in the first 24 h compared with Group 1 or 2. Group 3 had an increased risk for persistent organ failure (POF; odds ratio 2, 95% confidence interval [1.1–3.8], P = 0.03) compared with Group 1 after adjusting for difference in baseline clinical severity scores, there was no difference between Group 2 and Group 3 or Group 1. Multivariate regression analyses revealed that hemoconcentration and early faster fluid rate were risk factors for POF and mortality (both P < 0.05). Conclusions: Hemoconcentration is associated with faster fluid rate and POF in ward AP patients. Randomized trials comparing standardized early fast and slow fluid management is warranted. Abstract : In the present study, we investigated the relationship between hemoconcentration, early fluid therapy, and clinical outcomes in ward acute pancreatitis (AP) patients. We found that hemoconcentration is associated with faster fluid rate and POF in ward AP patients. Randomized trials comparing standardized early fast and slow fluid therapy is warranted.